Novel Immune Infiltrating Cell Signature Based on Cell Pair Algorithm Is a Prognostic Marker in Cancer - Zhang, Hao; Wang, Zeyu; Dai, Ziyu; Wu, Wantao; Cao, Hui; Li, Shuyu; Zhang, Nan; Cheng, Quan (Frontiers in Immunology, 2021)
Tumor-infiltrating immune cells (TIICs) have become an important source of markers for predicting clinical outcomes of cancer patients. However, measurements of cellular heterogeneity vary due to the frequent updated reference genomes and gene annotations. In this study, we systematically collected and evaluated the infiltration pattern of 65 immune cells. We constructed Immune Cell Pair (ICP) score based on the cell pair algorithm in 3715 samples and across 12 independent cancer types, among which ICP score from 6 cancer types was further validated in 2228 GEO samples. An extensive tumorigenic and immunogenomic analysis was subsequently conducted. As a result, ICP score showed robust reliability and efficacy in predicting patient’s survival in gliomas, pan-cancer samples, and six independent cancer types. Notably, ICP score correlated with genomic alteration features in gliomas. Moreover, ICP score exhibited remarkable association with multiple immunomodulators that could potentially mediate immune escape. Finally, ICP score predicted immunotherapeutic responses with high sensitivity, allowing a useful tool for predicting overall survival and guiding immunotherapy for cancer patients.